2017
DOI: 10.1111/tbed.12728
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and molecular characterization ofPorcine teschovirusin Hunan, China

Abstract: Porcine teschoviruses (PTVs) have been shown to be widely distributed in pig populations. In this study, 261 faecal and 91 intestinal content samples collected from pigs at 29 farms in Hunan, China, were tested for the presence of PTV by reverse transcription-polymerase chain reaction (RT-PCR). An overall PTV-positivity rate of 19.03% was detected by RT-PCR, and a high PTV infection rate was circulating in asymptomatic fattening and nursery pigs. In total, 40 PTV isolates (PTV-HuNs) were obtained. Alignment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
(82 reference statements)
0
8
0
Order By: Relevance
“…The subsequent epidemiological investigation showed that PSV was prevalent in southern China. The positive rate of PSV was about 45% in diarrhea samples and 21% in asymptomatic samples ( 7 , 25 ). Phylogenetic analysis showed the isolates in Hunan and Jiangxi varied from previous Chinese strains (cluster I) and formed another cluster (cluster II).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The subsequent epidemiological investigation showed that PSV was prevalent in southern China. The positive rate of PSV was about 45% in diarrhea samples and 21% in asymptomatic samples ( 7 , 25 ). Phylogenetic analysis showed the isolates in Hunan and Jiangxi varied from previous Chinese strains (cluster I) and formed another cluster (cluster II).…”
Section: Discussionmentioning
confidence: 93%
“…More and more information of its circulation in southern China has been provided since then. PSV was frequently detected in fecal samples in Hunan, China ( 7 , 29 ). In 2019, two different PSV strains, JXXY-a2 and JXXY-c, associated with only diarrhea, were isolated in Jiangxi Province ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the history, there were 4 recorded clinical PTV cases showing high mortality, they are 1930s in Czech with PTV-1 [ 7 ], 2009 in Republic of Haiti with PTV-1 [ 18 ], the same year in Dominica Republic with PTV-1 [18] and 2017 in Spain with PTV-13 [ 19 ]. Overall, in China, PTV associated diseases were mostly sporadic and mild and no PTV case showed mortality higher than 10% before [ 1 , 9 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, phylogenetic analysis of VP1 has been used as a reliable approach for characterizing the PTV genotypes [ 1 ]. Also, neutralizing epitopes mainly locate within VP1 and VP2 [ 1 , 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, phylogenetic analyses based on both the VP1 and the P1 gene sequences have proven to be reliable approaches for PTV genotyping (Cano-Gomez, Garcia-Casado, Soriguer, Palero, & Jimenez-Clavero, 2013;Cano-Gómez et al, 2011;Lin et al, 2012;Yang, Yu, et al, 2018b;Zell et al, 2001). Therefore, PTV-positive samples identified in the present study were selected, and their complete VP1 gene was sequenced using five different nested-PCR methods as previously described (Yang, Li, et al, 2018a).…”
Section: Genotype Porcine Teschovirus Species Teschovirus Bmentioning
confidence: 99%